PENGARUH VOLUNTARY DISCLOSURE, TIMELINESS LAPORAN KEUANGAN DAN PRAKTIK PERATAAN LABA TERHADAP EARNINGS RESPONSE COEFFICIENT - Intan Permatasari; Anik Malikah; Moh. Amin (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study aims to determine the effect of voluntary disclosure, timeliness of financial statements and income smoothing practices on earnings response coefficient. The population in this study are food and beverage companies listed on the Indonesian stock exchange. The sampling technique was a purposive sampling technique, the sample chosen was 6 companies. Data retrieved using the documentation method. The data analysis method is multiple regression analysis by SPSS version 14 software (Product Statistics and Solution services version 14). The test data used is the simultaneous hypothesis test (f), the coefficient of determination (R2), and partial hypothesis test (t). The results of the study indicate that simultaneously the independent variables significantly influence the dependent variable. Based on the test results of the coefficient of determination, the adjusted R value was 36.6% while the remaining 63.4% was influenced by other variables not included in this study. Based on the partial results that the voluntary disclosure and timeliness of financial statements affect the earnings response coefficient, while the practice of income smoothing does not affect the earnings response coefficient. Keywords: voluntary disclosure, timeliness of financial statements, income smoothing practices and earnings response coefficient